The Relationship Between Knowledge about Flood Disasters and Community Preparedness in RW 34, Bojongkulur Village, Bogor Regency - Silalahi, Martha Katarina; Sitorus, Seven; Suwarningsih; Wijaya, Alicia Salma (LPPM Universitas Mohammad Husni Thamrin, 2025)
Background: Flooding is a significant increase in river water flow from normal conditions due to continuous rain. This causes the riverbed to be unable to accommodate water, so that the water overflows and floods the surrounding area. In the context of hydrometeorological disasters, flooding is the most common phenomenon, and is supported by data from the National Disaster Management Agency (BNPB). Where this often causes great risks due to the lack of public knowledge about preparedness in facing flood disasters. The purpose of this study was to determine the relationship between knowledge about flood disasters and community preparedness in RW 34, Bojongkulur sub-district, Bogor district. Method: This study uses a quantitative design with an observational analytical method through a cross-sectional approach. The sample in this study was 116 people in RW 34, Bojongkulur sub-district. The instrument in this study was a questionnaire sheet with data analysis using the chi-square test. Results: The results of this study indicate that there is a relationship between knowledge about disasters and community preparedness with a p value of 0.029 (p < 0.05). Of the 116 respondents with good knowledge, more had very good preparedness (78.7%) compared to those with very poor preparedness (21.3%). Conclusion: There is a significant relationship between the level of knowledge about flood disasters and community preparedness. Respondents with good knowledge have good preparedness.